Acute Toxic Injuries of Rat's Visceral Tissues Induced by Different Oximes - Jaćević, Vesna; Nepovimova, Eugenie; Kuča, Kamil (Scientific reports, 2019)
Certain AChE reactivators, asoxime, obidoxime, K027, K048, and K075, when taken in overdoses and sometimes even when introduced within therapeutic ranges, may injure the different organs. As a continuation of previously published data, in this study, Wistar rats have sacrificed 24 hrs and 7 days after single im application of 0.1LD50, 0.5LD50 and 1.0LD50 of each reactivator, and examinated tissue samples were obtained for pathohistological and semiquantitative analysis. A severity of tissue alteration, expressed as different tissue damage scores were evaluated. Morphological structure of examinated tissues treated with of 0.1LD50 of all reactivators was comparable with the control group of rats. Moderate injuries were seen in visceral tissues treated with 0.5LD50 of asoxime, obidoxime and K027. Acute damages were enlarged after treatment with 0.5LD50 and 1.0LD50 of all reactivators during the next 7 days. The most prominent changes were seen in rats treated with 1.0LD50 of K048 and K075 (P < 0.001 vs. control and asoxime-treated group). All reactivators given by a single, high, unitary dose regimen, have an adverse effect not only on the main visceral tissue, but on the whole rat as well, but the exact mechanism of cellular injury remains to be confirmed in further investigation.
Keywords: Animals; orgánová specificita; Chemical Warfare Agents; vztah mezi dávkou a účinkem léčiva; Lethal Dose 50; Lung; oximy; biopsie; vnitřnosti; Molecular Structure; LD50; chemické bojové látky; Viscera; Histocytochemistry; molekulární struktura; Dose-Response Relationship, Drug; Oximes; žaludek; Biopsy; histocytochemie; krysa rodu Rattus; plíce; Organ Specificity; zvířata; Rats; Stomach